The Role of Government and Its Provision on the Quality of Education : The Case of Public Junior High School among Province in Indonesia Period 2000-2004 - Kharisma, Bayu (Buletin Studi Ekonomi, 2016)
This paper aims to examine the involvement of the government through the Law No. 20/2003 on National Education System of the quality of education, especially at the public junior high school level in various provinces in Indonesia during the period 2000-2004 and analyze government involvement characteristics associated with the provision using panel data analysis and literature review approach. The results showed that the role of government through routine expenditures has significantly compared to public junior high school development expenditure in improving the quality of education. In addition, Law no. 20/2003 on National Education System has a positive influence on the quality of education rate of public junior high schools in Indonesia. Meanwhile, the education level of secondary schools in Indonesia has a common resources good characteristic.
Keywords: Law No. 20/2003 on National Education System, Public Junior High School Level, Panel Data, Literature Review and common resources good characteristic